Effect of Gypsum and Etepon on Crop Yield Siamese Orange (Citrus Nobilis Var. Microcarpa L.) - A. A. Istri Tyagita Varenia; Ni Putu Anom Sulistiawati; Ni Komang Alit Astiari (Warmadewa University Press, 2021)
This study aims to determine the effect of Gypsum and Etepon on the yield of Siamese orange (Citrus nobilis Var Microcarpa. L) conducted in Belancan Village, Kintamani District, Bangli Regency from December 2020 to July 2021. This study used a randomized block design (RAK) with 2 factors arranged in a factorial manner. The first factor that was tried was the dose of gypsum fertilizer (G) which consisted of 4 levels, namely: G0 (0 g/tree), G1 (250 g/tree), G2 (500 g/tree) and G3 (750 g/tree. While the second factor is the concentration of etepon (E) which consists of 3 levels, namely: E0 (0 ml/l water/tree), E1 (0.75 ml//l water/tree) and E2 (1.5 ml/l water)/tree). Thus, there were 12 combination treatments, each of which was repeated 3 times so that 36 citrus trees were needed. The results showed that the interaction between the dose of gypsum and the concentration of etepon had no significant effect on all observed variables. The highest harvested fruit weight per tree was obtained at a dose of gypsum 750 g/tree which was 6.32 kg or an increase of 70.35% when compared to treatment without gypsum which was only 3.71 kg. The highest harvested fruit weight per tree was obtained in the etepon treatment with a concentration of 1.5 ml/l/tree, which was 6.54 kg, an increase of 51.38% compared to the treatment without etepon, which was only 4.32 kg. Keywords: dose, etepon, gypsum, Siamese orange, yield